Emigración internacional en ecuador: Un estudio en la capital de la república - Herrera Acosta, Carlos Ernesto (2021)
Ecuador since the beginning of its republican life (1830), has been a territory where foreigners from various parts of the world have arrived; in 1999 this social phenomenon was increased by the arrival of Cubans and Colombians; In 2017, foreign emigration experienced a growth not seen in other times due to the flow of Venezuelans, foreigners who emigrate to Ecuador, have chosen as their residence the main provinces and cities, such as: Pichincha - Quito, Guayas - Guayaquil, Azuay - Cuenca The article aims to analyze international emigration, to point out some social, economic and political characteristics; the analysis unit is located in the city of Quito, belonging to the Pichincha Province, Republic of Ecuador; Due to its characteristics, it is a socio-legal investigation, with a qualitative approach, non-experimental design, basic type, the population involved is made up of 310 emigrants and 10 authorities related to human mobility; This indicates that in recent years, the migratory flow has grown precisely, a fact that has influenced the increase in social, economic and political problems.